Third trimester maternal vitamin D and early childhood socioemotional development. Issue 3 (8th December 2020) - Francis, Ellen C.; Charron, Elizabeth; Li, Mengying; Chen, Liwei; Mayo, Rachel; Butler, Linda S.; Rennert, Lior
Abstract: Background: Whether maternal vitamin D affects offspring socioemotional development in early childhood has been underexplored. Objectives: This study examined associations between maternal vitamin D during in the 3rd trimester and offspring socioemotional development between 30 and 59 months. Methods: Data from 87 maternal‐offspring pairs enrolled in the National Children's Study were used. Total plasma maternal vitamin D (25‐hydroxyergocalciferol + 25‐hydroxycholecalciferol) was measured between 28 and 35 gestational weeks and categorised as quartiles (Q). Multivariable regression models, adjusting for maternal race/ethnicity, education, and prepregnancy body mass index (BMI [kg/m 2 ]), were used to estimate the association between vitamin D and offspring scores on the Brief Infant‐Toddler Social and Emotional Assessment (BITSEA). Results: The mean (standard deviation) vitamin D concentration was 86.5 (27.8) nmol/L. The median (range) BITSEA problem score was 6.0 (0.0‐30.0), and competence score was 19.0 (7.0‐22.0). Maternal vitamin D was inversely related to offspring problem scores. Compared to offspring of women with 25(OH)D in Q1, offspring problem scores were −4.80 (95% confidence interval [CI] −8.29, −1.33) units lower for Q2 vs Q1, −5.64 (95% CI −9.60, −1.68) units lower for Q3 vs Q1, and −4.70 (95% CI −8.59, −0.82) units lower for Q4 vs Q1. Vitamin D was not associated with offspring competence score. Conclusions: Higher maternal vitamin D was associated with lower offspring behaviour problems and not associated with socioemotional competence. These data indicate the association of maternal vitamin D and offspring development may be dependent on the specific developmental component being investigated.